The Impact of Perceived Value on Engagement, Purchase Intention, and Continuance Usage Intention: A PLS-SEM Study on Social Commerce Live Streaming Context - Muhammad Fajar Ramadhoni; Grandys Frieska Prassida (Jurnal Sistem Informasi Bisnis, 2025)
This study aims to analyse the factors influencing customer engagement in social commerce live streaming, specifically on the TikTok Shop platform, and their impact on purchase intentions and continuance usage intention. The significance of this research lies in the rapid development of social media applications within the social commerce sector, which presents new opportunities for brands to interact directly with users through live streaming features. A quantitative research approach was employed, utilizing survey techniques to collect data from respondents who are active users of the TikTok Shop platform in Indonesia and engage with its live streaming feature. The data were analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) method. The results indicate that the hedonic, symbolic, and interactivity values of live streaming positively influence customer engagement, whereas utilitarian values have no significant effect. Moreover, customer engagement positively affects purchase intentions and continuance usage intentions. These findings underscore the critical role of emotional and interactive aspects of live streaming in fostering customer engagement, which subsequently enhances purchase intentions and sustained usage. This research offers valuable insights into the development of digital marketing and user interaction strategies in the context of social commerce.